Development of Smart Meter to Monitor Real Time Energy Consumption for Sustainability - Nebrida, Alan P.; Amador, Chavelita D.; Madiam, Clyed M.; S. Ranche, Glenn John (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study constructed a Smart Energy Meter where energy consumption can be viewed by the consumers based on rreal time using data from smart meters. Its goals are to increase productivity, make readings more precise, and take less time to determine an individual residence’s energy consumption. The device is made up of the PZEM-016 AC Energy Meter, RS-485 UART Serial Converter, NodeMCU ESP8266, Blynk IoT Application, Arduino Uno R3, and LCD Arduino Keypad Module Shield Board. The PZEM-016 is used in this smart energy meter to measure voltage, current, power, frequency, power factor, and energy consumption. Because it lacks its own display, an RS-485 was utilized to communicate with the NodeMCU and Arduino Uno. The NodeMCU sends the parameters to Blynk IoT App as long as it is connected to a fixed mobile WiFi. The Blynk will then display a real-time measurement of the parameters. The Arduino Uno is programmed to display the parameters to the LCD Keypad Module. The device was tested in an actual household. The researchers conducted 48-hour observation on the household where the energy displayed in the Blynk IoT App and the LCD display matches at approximately 9 kWh which is the same as the actual energy meter of the house that is 9kWh. The device is also tested on different appliances which resulted in the same energy consumption in both the Blynk IoT App and LCD display with the ratings of the appliances. The device was found functional.